Presence of Anxiety and Depression Symptoms Affects the First Time Treatment Efficacy and Recurrence of Benign Paroxysmal Positional Vertigo - Wei, Wei; Sayyid, Zahra N.; Ma, Xiulan; Wang, Tian; Dong, Yaodong (Frontiers in Neurology, 2018)
Objectives: To investigate the possible effects of anxiety and/or depression symptoms on the treatment outcomes and recurrence of benign paroxysmal positional vertigo (BPPV). Methods: This is a retrospective study conducted in a single institution. 142 consecutive patients diagnosed with idiopathic BPPV at the Department of Otology in Shengjing Hospital of China Medical University between October 2016 and July 2017 were retrospectively reviewed. 127 patients were finally included in this study. Zung self-rating anxiety scale (SAS) and Zung self-rating depression scale (SDS) were used to evaluate the presence of anxiety and/or depression, respectively, in our BPPV patients. A significant score (at or above 50 for SAS and 53 for SDS) represents the presence of clinically significant symptoms. Two-tailed Student’s t-test, χ2 test, and logistic regression analysis were used as appropriate. A p-value less than 0.05 was considered statistically significant. Results: The prevalence of anxiety and/or depression symptoms in BPPV patients in the present study was 49.61%. The effectiveness of the first time canalith-repositioning maneuver (CRM) was 70.08%. With weekly follow-up treatments of CRM, the success rate increased to 97.64% by 1 month. The total recurrence rate at 6-month follow-up post-cure was 14.17%. Holding all other variables constant, patients with psychiatric symptoms (Relative-risk ratio: 3.160; p=0.027) and patients with non-posterior semicircular canal (PSC) involvement (Relative-risk ratio: 7.828, p=0.013) were more likely to experience residual dizziness (RD) even after effective CRM treatment. Psychiatric symptoms (Relative-risk ratio: 6.543; p=0.001) and female gender (Relative-risk ratio: 4.563; p=0.010) are risk factors for the failure of first time CRM. In addition, BPPV patients with psychiatric symptoms were significantly more likely to experience recurrences within the first six months after a successful maneuver. Conclusions: Anxiety-depression status significantly reduced the efficacy of the first time CRM and increased the risk for recurrence. Other factors such as female gender and non-PSC involvement are also susceptible risk factors for BPPV patients to require multiple treatments and experience delayed recovery. A screening for psychiatric symptoms in BPPV patients and active treatment of these symptoms would benefit both physicians and patients in understanding and improving the prognosis of the disease and treatment options.